(untitled) (AYUSHDHARA, 2025)
Skin diseases have been widely described in Ayurveda under the broad term “Kushta.” Among these, Vipadika is classified as a Kshudra Kushta (minor skin disorder) and is primarily associated with an imbalance of Vata and Kapha doshas. It is characterized by painful cracks, excessive dryness, roughness, itching and occasional bleeding, mainly affecting the palms and soles. Contemporary treatment options often lead to temporary relief with frequent recurrence, leading patients to seek alternative therapies. The present case report aims to assess the therapeutic efficacy of Ayurvedic management in treating Vipadika. A 51-year-old male presented with fissures, dryness, roughness in both sole and pain, itching; diagnosed as Vipadika. The treatment approach exclusively involved Shamana Chikitsa, including the oral administration of Avapidak snehpan, Arogyavardhini vati, Gokshuradi gugul, Kaishor gugul, Phalatrikadi kadha, combination of Yashtimadhu guduchi shunthi haritaki churna. Topical care was provided by washing the affected area with lukewarm water and application of Kailas jivan lotion. Pathya-Apathya regarding diet and lifestyle also suggested. The patient’s response was assessed over ten weeks, with post treatment follow-up of four weeks to assess symptom improvement and patient-reported outcomes. This case highlights the potential effectiveness of Ayurvedic interventions in managing Vipadika, offering a promising alternative or complementary approach for conditions resembling palmoplantar psoriasis, especially in cases prone to relapse.